2021
DOI: 10.1016/j.ijid.2020.10.088
|View full text |Cite
|
Sign up to set email alerts
|

Association of schistosomiasis and HIV infections: A systematic review and meta-analysis

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 72 publications
0
37
0
Order By: Relevance
“…Urogenital schistosomiasis, caused by the blood fluke Schistosoma haematobium, is one of the most neglected tropical diseases (NTDs) worldwide, afflicting more than 100 million people, particularly in Africa and the Middle East [1,2]. This disease is transmitted to humans via aquatic snails (intermediate hosts) typically of the genus Bulinus [3] and is characterised by granulomata, fibrosis and calcification in the urinary bladder wall and other parts of the urogenital tract [4,5], with complications including increased susceptibility to HIV/AIDS [6] and squamous cell carcinoma of the urinary bladder [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Urogenital schistosomiasis, caused by the blood fluke Schistosoma haematobium, is one of the most neglected tropical diseases (NTDs) worldwide, afflicting more than 100 million people, particularly in Africa and the Middle East [1,2]. This disease is transmitted to humans via aquatic snails (intermediate hosts) typically of the genus Bulinus [3] and is characterised by granulomata, fibrosis and calcification in the urinary bladder wall and other parts of the urogenital tract [4,5], with complications including increased susceptibility to HIV/AIDS [6] and squamous cell carcinoma of the urinary bladder [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed this gap in routine detection of FGS within current primary health care settings means most endemic communities are still unaware of the existence or diagnosis of this important gender-specific manifestation of urogenital schistosomiasis [24][25][26][27]. The need to readdress this unfortunate oversight is important as there is unequivocal evidence of the clear link between FGS, and raised acquisition of Human Immunodeficiency Virus (HIV) [28][29][30] and cervical cancer [22]. The Central Africa region is a known host for the Schistosoma haematobium blood flukes, with high endemicity in several countries like Gabon [31], Democratic Republic of Congo [32], Central African Republic and Cameroon [33].…”
Section: Introductionmentioning
confidence: 99%
“…A study looking across 43 sub-Saharan countries found that for every S. haematobium infection per 100 individuals, there was a relative increase of 2.9% in HIV prevalence suggesting an association between infection with S. haematobium and HIV (14). The local in ammatory response to the parasite eggs includes HIV target cells (CD4 + T lymphocytes and macrophages)( 22) and coupled with the friable epithelium and lesions which can cause bleeding during coitus creates a permissive setting for HIV transmission (23). Therefore, addressing schistosomiasis can improve women's overall reproductive health and decrease vulnerability to other important reproductive health threats such as HIV.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, addressing schistosomiasis can improve women's overall reproductive health and decrease vulnerability to other important reproductive health threats such as HIV. Recently, a WHO Technical Working Group on HIV and Schistosomiasis reviewed and summarized the evidence of the association between HIV and schistosomiasis and put forth concrete actions to control the HIV/schistosomiasis syndemic in adolescent girls and young women (AGYW) (3,23). In their systematic review(23) the authors, members of the working group, highlighted the need for training in health care workers as a critical gap to improve the condition of AGYW suffering from both diseases.…”
Section: Introductionmentioning
confidence: 99%